One new species of Ptomaphaminus Perreau, 2000 (Coleoptera: Leiodidae: Cholevinae: Ptomaphagini) from a granitic subterranean environment in Vietnam - Perreau, Michel; Faille, Arnaud (Zootaxa, 2015)
Ptomaphaminus granophilus n. sp. from Vietnam is described and illustrated. The special subterranean biotope of this species, deep interstices in a granitic blockfield, is emphasized.